POLA KOMUNIKASI ORGANISASI KESATUAN AKSI MAHASISWA MUSLIM INDONESIA (KAMMI) DALAM MENINGKATKAN EKSISTENSINYA DI KOTA BEKASI - Siskamia Oktafiani; Budi Suswanto (Interpretasi: Communication & Public Relations, 2022)
Organizational communication is the delivery of messages or information from one party to another within an organization to achieve certain goals. An organizational communication pattern is a method of communicating that involves conveying a message from the sender to the recipient in such a way that it can be understood. This research is motivated by thoughts related to communication phenomena that occur within the Indonesian Muslim Student Action Unit (KAMMI) organization and the researcher's desire to find out how the communication pattern used by KAMMI explains its existence in Bekasi City. The research method used in this study is a qualitative research method using an interpretive paradigm. Data collection was obtained through observation, interviews, and documentation. The results of this study are the communication pattern used by KAMMI Bekasi City, namely the organizational communication pattern run by KAMMI Bekasi City in accordance with Joseph A. Devito's theory, and several organizational activities that are able to support the existence of the Bekasi City KAMMI organization.